Концептуальные положения"зеленой смарт" промышленности - Заниздра, М.Ю. (Економіка промисловості, 2018)
Обобщены определения "углеродной", "зеленой" и "смарт" промышленности и установлено текущее распределение их удельных весов в современной структуре глобальной экономики. Оценены перспективы расширения и слияния сфер влияния "зеленой" и "смарт" промышленности как конгруэнтных стратегий устойчивого развития. На основе критического анализа концепций "зеленой" и "смарт" промышленности выдвинуты гипотезы относительно ключевых особенностей производимого продукта, организации производственного процесса, драйверов развития, стратегических приоритетов и подходов к их достижению, характерных для "зеленой смарт" промышленности как отдельного направления экономической деятельности. Узагальнено визначення і встановлено поточний розподіл питомої ваги "вуглецевої", "зеленої" та "смарт" промисловості у структурі сучасної глобальної економіки. Оцінено перспективи розширення та злиття сфер впливу "зеленої" та "смарт" промисловості як конгруентних стратегій сталого розвитку. На основі критичного аналізу концепцій "зеленої" та "смарт" промисловості запропоновано гіпотези щодо ключових особливостей виробленого продукту, організації виробничого процесу, драйверів розвитку, стратегічних пріоритетів і підходів до їх досягнення, характерних для "зеленої смарт" промисловості як окремого напряму економічної діяльності. In the paper the main distinctive features of the "green smart" industry as a sector of economic activity combining the principles of ecologization and cyberphysical transformation of business processes are formulated, as well as the key factors, contributing to the merger of the subject areas of the "green" and "smart" industry are determined.Due to the common strategic goal (achieving sustainable development), the material base (production assets) and the main driver of progress (technical and technological innovations), the hypothesis of the congruence of "green" and "smart" development strategies was justified, including such aspects as that new cyberphysical technologies, on the one hand, offer new solutions to the problems of sustainable development, and, on the other hand, form new threats.The definitions have been summarized and the current distribution of the relative share of the "carbon", "green" and "smart" industries in the current structure of the global economy has been established. The prospects for expanding and merging the spheres of influence of the "green" and "smart" industries as congruent strategies for sustainable development were evaluated. It was also argued, that the potential "smart" industry would seek to meet the standards of "green" industry, while the "green" one would acquire the properties of "smart" as the fourth industrial revolution progressed and digital innovations spread across all spheres of public life. Based on a critical analysis of the concepts of the "green" and "smart" industries, hypotheses regarding the key features of the product, the organization of the production process, the drivers of development, strategic priorities and approaches to their achievement, characteristic of the "green smart" industry as a separate direction of economic activity, have been developed. They include creation of knowledge-intensive "environmentally friendly" product focused on a specific client; provision of remote control and monitoring of automated high-tech business processes in real time; strategic business planning to minimize the man-made burden on the environment by maximizing intellectual capital, carried out on the basis of "big data"; priority of the best "environmentally friendly" advanced technologies.The reference standard of the "green smart" industry is a cyberphysical network of interconnected high-tech productions-symbionts operating on the principle of conditionally closed preferential loops of recycling of resources similar to the natural cycle of substances in self-regulatory ecosystems.The author also took into account that the concept of congruence of "green" and "smart" industrial development strategies is not indisputable because of objective fundamental differences in the purpose of "green" and "smart" strategies, out of the key approaches and due to production priorities, as well as the properties of the final product, which affect the consumer value of "green" and "smart" products and have a significant impact on the speed of distribution of these strategies on the market. However, in the long term, both directions have sufficient potential for further development and, accordingly, unification.